Exercise and lung cancer surgery: A systematic review of randomized-controlled trials. (December 2020) - Himbert, Caroline; Klossner, Nicole; Coletta, Adriana M.; Barnes, Christopher A.; Wiskemann, Joachim; LaStayo, Paul C.; Varghese Jr., Thomas K.; Ulrich, Cornelia M.
Graphical abstract: Abstract: Lung cancer patients undergoing surgery are often left physically deconditioned and/or with functional deficits. Exercise interventions may improve pulmonary and physical function before and after lung resection. We conducted a systematic review of randomized-controlled trials (RCTs) testing the impact of pre-, post-, and combined pre-and-post surgery exercise interventions on physical and pulmonary function in lung cancer patients. Exercise pre-surgery seems to substantially improve physical and pulmonary function, which are factors associated with improved ability to undergo surgery while reducing post-surgery complications. Evidence is inconsistent for post-surgery interventions, reporting no or moderate effects. Results from pre-and-post surgery interventions are limited to one study. In conclusion, pre- and post-surgery exercise interventions, individually, have shown beneficial effects for lung cancer patients undergoing surgery. The impact of interventions combining both pre- and post-surgery exercise programs remains unknown. More evidence is needed on the ideal exercise setting, and timing across the lung cancer care continuum.